Ferromagnetic Nickel as a Sustainable Reducing Agent for Tin–Lead Mixed Perovskite in Single‐Junction and Tandem Solar Cells - Doyun Im; Passarut Boonmongkolras; Yeonghun Yun; Sung Woong Yang; Sunwoo Kim; Jungchul Yun; Rajendra Kumar Gunasekaran; You‐Hyun Seo; Nam Joong Jeon; Gill Sang Han; Sangwook Lee (Advanced Science)
Abstract Narrow‐bandgap (NBG) Sn–Pb mixed perovskite solar cells (PSCs) represent a promising solution for surpassing the radiative efficiency of single‐junction solar cells. The unique bandgap tunability of halide perovskites enables optimal tandem configurations of wide‐bandgap (WBG) and NBG subcells. However, these devices are limited by the susceptibility of Sn2+ in the NBG bottom cell to being oxidized to Sn4+, creating detrimental Sn vacancies. Herein, a novel approach that replaces Sn particles with Ni particles is introduced as the reducing agent for Sn–Pb mixed perovskite precursor solutions. The ferromagnetic properties of Ni enable simple magnetic filtration, eliminating the filtration issues associated with Sn particles. Ni particles can be reused up to five times without significantly affecting the PSC's performance. Additionally, Ni effectively mitigates the oxidation of Sn2+ due to its low reduction potential (−0.23 V), thereby enhancing device performance. Single‐junction Sn–Pb mixed PSCs prepared using Ni achieve a power‐conversion efficiency (PCE) of 22.29%, retaining over 90% of their initial efficiency after 1250 h. Furthermore, Ni‐based all‐perovskite tandem solar cells combining 1.77 eV WBG top cells with 1.25 eV NBG bottom cells achieve a remarkable PCE of 28.13%. Thus, the proposed strategy can facilitate the commercialization of all‐perovskite tandem devices.